2017
DOI: 10.1136/tobaccocontrol-2016-053552
|View full text |Cite
|
Sign up to set email alerts
|

Flavour chemicals in a sample of non-cigarette tobacco products without explicit flavour names sold in New York City in 2015

Abstract: BackgroundYouth who experiment with tobacco often start with flavoured products. In New York City (NYC), local law restricts sales of all tobacco products with ‘characterising flavours’ except for ‘tobacco, menthol, mint and wintergreen’. Enforcement is based on packaging: explicit use of a flavour name (eg, ‘strawberry’) or image depicting a flavour (eg, a fruit) is presumptive evidence that a product is flavoured and therefore prohibited. However, a tobacco product may contain significant levels of added fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…Compared with cigarette smoke, different types and values of pollutants are produced in response to waterpipe smoking. High exposure to high molecular weight PAHs and benzene, but lower exposure to propylene oxide, acrolein, acrylonitrile, butadiene-1,3, nitrosamines, ethylene oxide, and low molecular weight PAHs have been reported in tobacco cafés as compared with cigarette cafés 38 . Different rates of pollutants production by different tobacco products have been observed in previous studies 39,40 .…”
Section: Resultsmentioning
confidence: 99%
“…Compared with cigarette smoke, different types and values of pollutants are produced in response to waterpipe smoking. High exposure to high molecular weight PAHs and benzene, but lower exposure to propylene oxide, acrolein, acrylonitrile, butadiene-1,3, nitrosamines, ethylene oxide, and low molecular weight PAHs have been reported in tobacco cafés as compared with cigarette cafés 38 . Different rates of pollutants production by different tobacco products have been observed in previous studies 39,40 .…”
Section: Resultsmentioning
confidence: 99%
“…These are summarized in Additional file 1: Table 1. Of the nine excluded studies, one study found that adolescents had a 37% lower odds of ever trying flavored tobacco products and a 28% lower odds of ever using tobacco products post ban [54], two studies found that sales of other tobacco products fell [55,56], and six considered compliance [57][58][59][60][61][62]. The studies of compliance indicated mixed levels of compliance, with flavor products still available in up to 50% of retailers that were not allowed to sell flavored tobacco and smaller stores often continuing to carry banned products with staff oblivious to the ban [58,[60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Local, state, and national policymakers should consider bans on cigarillo packaging with overt flavor descriptors or imagery that connotates a flavor, or packaging that implies a certain flavor through generic descriptors such as “Tropical” [ 37 ]. Prohibiting non-overt flavor descriptors is particularly important, as the tobacco industry has been able to circumvent flavor bans by removing explicit flavor names while maintaining flavor chemicals in products [ 52 ]. Further, bans on flavor descriptors and associated flavor imagery could be accompanied by bans in actual product flavoring, similar to the flavor bans on cigarettes [ 53 ].…”
Section: Discussionmentioning
confidence: 99%